Epic! Homer and the Nibelungenlied in Translation - Boyle, M; Flacke, P; Powell, T (Taylor Institution Library, 2024)
The catalogue to the exhibition ‘Epic! Homer and the Nibelungenlied in Translation’ in the Taylor Institution Library, Oxford, traces what began, and time and again turned out to continue, as a shared reception. It showcases material from the Taylor Institution Library’s collections, alongside additions from the Bodleian Library and from private collections. Building on the 2022 exhibition ‘Violent Victorian Medievalism’ curated by Mary Boyle, it shines particular light on adaptations for children and to the fraught topic of women and violence. The books featured tell the story of the various attempts to assert ownership of these epics. This was not simply a matter of translating the texts, but of claiming them for different national and pre-national identities, for specific ideas of masculinity and femininity, for militaristic agendas and racist ideologies, but also, more recently, for feminist and queer causes. Three essays by Mary Boyle, Philip Flacke, and Timothy Powell shine additional spotlights on various stages of the epics’ reception in four centuries. This starts with the judgement by the Swiss critic Johann Jakob Bodmer ‘Dieses Gedicht hat etwas iliadisches’ – ‘There is something Iliad-like about this poem’. He set the tone for public perceptions of the Nibelungenlied shortly after its rediscovery in the mid-eighteenth century. Looking at the thirteenth-century German epic in terms of Homer took root. Future generations had to grapple with this, some willingly, others reluctantly. As late as the 1970s, when the German writer Franz Fühmann attempted to re-envision the Nibelungenlied in the light of national identity in the GDR, he found it necessary first of all to distance himself from the trope of the ‘German Iliad’. What does this trope mean exactly? What are the implications of looking at the Nibelungenlied through the prism of the Homeric epics – and vice versa? In what way did it affect dealing with the texts, with ideas about the epic and ideas about things which have been tied to it in different ways – about gender, nation, violence? And how do these readings still inform our world today? The essays are accompanied by two extensive appendices that chronicle the inexhaustible possibilities of telling the same story as well as the sometimes bizarre and sometimes frightening endorsements and critiques of comparing the Nibelungenlied to Homer. Concluding the volume is a catalogue of the Homeric Fragments in the collection of the Bodleian Library, curated by Nigel Wilson and Peter Tóth. The book is part of the ‘Cultural Memory’ series of the ‘Treasures of the Taylorian’, which aims to bring the books from the collections into dialogue with wider topics outside. It accompanies the workshop ‘The Reading and Reception of the Homeric Poems and the Nibelungenlied in Germany and Europe from the Eighteenth Century to the Present’, co-hosted by the Meran Academy and Oxford Medieval Studies.